ANALISIS STRATEGI PENEGAKAN HUKUM DALAM RANGKA MEWUJUDKAN MASYARAKAT SADAR HUKUM DI KABUPATEN LAMPUNG UTARA - Tami Rusli; MULIAWATI NURTYA KUSNADI (Universitas Bandar Lampung (UBL), 2021)
The safety condition and level of traffic law compliance of the community who understand legal regulations will affect the safety condition and level of communitytraffic law compliance as well as strategically. The problem is what is the law enforcement strategy in order to create a law-aware society based on Law No. 22 of 2009 concerning Road Traffic and Transportation ? and what are the inhibiting factorsin law enforcement in order to create a law-aware society based on Law Number 22 of2009 concerning Road Traffic and Transportation? The research method is through anormative juridical approach and an empirical approach using secondary data andprimary data, then qualitative data analysis is carried out . The results of the research,that the law enforcement strategy in order to realize a litigious society based on LawNumber 22 Year 2009 regarding Traffic and Road Transportation , the strategy of preemptive,the strategy of preventive and strategies repressive.Furthermore, the inhibiting factors in law enforcement in order to create a law-conscious society based on Law Number 22 of 2009 concerning Road Traffic and Transportation, include legal factors, law enforcement factors,facilities andfacilitiesfactors,community factorsandculturalfactors.Thesuggestion isthat thepublicshouldhaveawarenesstoobeytheapplicablelaws andregulations sothattheleveloftrafficviolationscanbereduced.